Effects of dietary fiber on the growth performance, carcass characteristics, and carcass fat quality in growing-finishing pigs - Asmus, Matthew Duane (Kansas State University, 2012)
Three experiments used 777 pigs to study the effects of fiber source; wheat middlings (midds), dried distillers grains with solubles (DDGS), and choice white grease (CWG), and reduction strategies for growing and finishing pigs. Also a fourth study utilizing 1,360 pigs was conducted to determine the effect of immunocastration (IC) and DDGS withdrawal on growth performance, carcass characteristics, fatty acid analysis, and iodine value (IV) of pork fat depots in growing and finishing pigs. Experiment 1 determined that the ingredient source of fiber (wheat middlings or DDGS) was more important than NDF level alone, for characterization of growth, carcass, and yield responses. Experiment 2 showed that a short (23 d) fiber reduction strategy was successful at fully recovering yield loss; however, a longer reduction (47 d) was necessary for further improvements in carcass fat quality (IV). Experiment 3 further proved that yield loss can be recovered with a short fiber reduction strategy (19 d), and that adding energy from CWG during the fiber reduction period can improve feed efficiency, but was unsuccessful at further improving carcass yield or carcass fat quality. Experiment 4 showed that carcass yield was lower for IC pigs than barrows regardless of dietary DDGS or withdrawal strategy. Also pigs fed 30% DDGS throughout had decreased carcass yield; however, withdrawing DDGS from the diet on d 74 was effective at recovering the yield loss. While DDGS withdrawal strategy was successful at lowering IV, but was unsuccessful at fully lowering IV to values of pigs fed the control diet throughout. Iodine values were somewhat variable within fat depot, showing the jowl and clear plate fat were less accurate in showing changes from the diet, most likely due to the fact they are deposited earlier and are slower to turnover. Iodine value tended to be greater for IC pigs than barrows on d 107, but by d 125 there were no differences in IV between IC and barrows. This dramatic improvement from d 107 to 125 could be caused by the dilution of unsaturated fatty acids, specifically C18:2 and C18:3, due to the rapid deposition of fat in IC pigs.
Keywords: Finishing pigs; Fiber; NDF; Wheat middlings; DDGS; Improvest; Animal Sciences (0475)